Acute thrombus formation on phosphorilcholine surface modified flow diverters - Marosfoi, Miklos (J Neurointerv Surg, 2018)
PURPOSE: Thromboembolic complications remain a limitation of flow diverting stents. We hypothesize that phosphorilcholine surface modified flow diverters (Pipeline Flex with Shield Technology, sPED) would have less acute thrombus formation on the device surface compared with the classic Pipeline Embolization device (cPED). METHODS: Elastase-induced aneurysms were created in 40 rabbits and randomly assigned to receive cPED or sPED devices with and without dual antiplatelet therapy (DAPT) (four groups, n=10/group). Angioplasty was performed to enhance apposition and create intimal injury for a pro-thrombotic environment. Both before and after angioplasty, the flow diverter was imaged with intravascular optical coherence tomography. The outcome measure was the number of predefined segments along the implant relative to the location of the aneurysm with a minimum of 0 (no clot formation) and maximum of 3 (all segments with thrombus). Clot formation over the device at ostia of branch arteries was assessed as either present or absent. RESULTS: Following angioplasty, the number of flow diverter segments with clots was significantly associated with the flow diverter (p<0.0001), but not with DAPT (p=0.3872) or aneurysm neck size (p=0.8555). The incidence rate for clots with cPED was 1.72 times more than with sPED. The clots on the flow diverter at the location corresponding to side branch ostia was significantly lower with sPED than with cPED (OR 0.180; 95% CI 0.044 to 0.734; p=0.0168), but was not associated with DAPT (p=0.3198). CONCLUSION: In the rabbit model, phosphorilcholine surface modified flow diverters are associated with less thrombus formation on the surface of the device.